2016
DOI: 10.1111/petr.12831
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors, and prognosis of capillary leak syndrome in pediatric recipients of stem cell transplants: a retrospective single‐center cohort study

Abstract: CLS involves sudden loss of intravascular fluids into the interstitial spaces. CLS was described as a possible complication after SCT. Few studies report the incidence of CLS in pediatric populations. We aimed to assess CLS incidence, its risk factors, and impact on the survival. The clinical charts of patients <18 years of age transplanted at our institution between 2002 and 2012 were reviewed. CLS was defined by weight gain >3% in 24 hours and positive intake balance despite furosemide administration. In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…A weight increase of at least 3% during 24 h is often used as a part of the diagnostic criteria for capillary leak syndrome [46]. This definition was used in a recent study of capillary leak syndrome in elderly allotransplanted pediatric patients whereas a weight criteria alone was used for the smallest children; these authors then described an association between capillary leak syndrome and decreased survival [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A weight increase of at least 3% during 24 h is often used as a part of the diagnostic criteria for capillary leak syndrome [46]. This definition was used in a recent study of capillary leak syndrome in elderly allotransplanted pediatric patients whereas a weight criteria alone was used for the smallest children; these authors then described an association between capillary leak syndrome and decreased survival [47].…”
Section: Discussionmentioning
confidence: 99%
“…There is no generally accepted definition for capillary leak syndrome [49], but a definition including at least 3% weight gain during 24 h may be used [46]. As an alternative we therefore analyzed the impact of the maximal weight gain, and in contrast to the definition of capillary leak syndrome our parameter could be handled as a continuous variable in the survival analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The average of the Ct value was calculated after the PCRs were run in duplicate for each sample. The cel-miR-39 value from the duplicate was used as the internal control [13, 30]. The relative expression of each miR-146a after normalization to cel-miR-39 is displayed as2 -[Ct (miRNA)- Ct (cel-miR-39)] .…”
Section: Methodsmentioning
confidence: 99%
“…Allogeneic HCT from an unrelated donor, G-CSF administration, and intensive chemo/radiotherapy have been suggested as possible risk factors for CLS development [56,57]. A recent study in pediatric patients undergoing HCT [58] confirmed historical results suggesting that severe infection is associated with CLS, independently from HCT. This association is supposed to rely upon the endothelial damage induced by the cytokine storm that occurs in severe infection, which is believed to be crucial in the development of CLS.…”
Section: Evidence On the Endothelial Origin Of Vascular Endothelial Smentioning
confidence: 80%